Analysis of the Influence of Hedonistic Shopping Motivation and Flash Sale Strategy on Shopee Users' Consumer Buying Interest (Empirical Study on Students of the Universitas Muhammadiyah Lamongan) - Suyitno; Erna Nur Faizah; Betta Cahya Islami (ECO-BUILD, 2025)
This study aims to analyze the influence of hedonic shopping motivation and flash sale strategies on the buying interest of Shopee consumers among students at the Universitas Muhammadiyah Lamongan (UMLA). The development of digital technology has transformed consumption patterns, particularly in online shopping, with Shopee emerging as one of the largest e-commerce platforms in Southeast Asia. Hedonic shopping motivation, which refers to the pleasure and emotional satisfaction derived from shopping, along with flash sale strategies offering significant discounts for a limited time, are hypothesized to significantly influence buying interest. This research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 70 UMLA students who actively shop on Shopee, particularly during flash sale events. Sampling techniques included purposive sampling and accidental sampling, with data analysis conducted using multiple linear regression. The results indicate that hedonic shopping motivation (X1) and flash sales (X2) significantly affect buying interest (Y), with regression coefficients of 0.418 (Sig. 0.000) and 0.574 (Sig. 0.000), respectively. The coefficient of determination (R²) of 0.692 suggests that these two variables contribute 69.2% to buying interest, while the remaining 30.8% is influenced by other factors outside the research model. The research instruments were reliable (Cronbach's Alpha > 0.6), and the data were normally distributed (Asymp. Sig. 0.085 > 0.05). These findings highlight the importance of considering consumer psychological aspects and promotional strategies in e-commerce marketing, particularly for the student segment. This study provides empirical contributions to the development of Shopee's marketing strategies and the literature on consumer behavior in the context of online shopping in Indonesia.